Exploring the elements of Muslim-friendly airline services - Harum, Ahmad Aiman; Abdul Halim, Siti Norhamimah; Jamaludin, Mohammad Aizat; Muflih, Betania Kartika (HH Publisher, 2018)
Muslim-Friendly Airline (MFA) is an emerging trend in the aviation industry whereby efforts of integrating shariah elements into the airline industry are established through shariah-compliant airlines. However, to date, such establishment is selfproclaimed due to lack of specific guidelines issued by authorities. Research in this area is also still in its infancy thus this paper attempts to explore the important shariah-guided elements that should be available in an MFA service. Data was gathered through library research and qualitative analysis was carried out utilising secondary data obtained. Several important elements for MFA were found, namely the availability of halal food and beverages, facilities to perform prayer, notice of prayer time, ablution, qiblah direction, recitation of du’a, dress code, segregation of gender and shariah-compliant entertainment. These elements can be ranked into essential, complimentary and embellishment as guided by shariah principles; and are recommended to be fulfilled by airlines towards establishing Muslim-friendly services.